1970
DOI: 10.1002/app.1970.070140506
|View full text |Cite
|
Sign up to set email alerts
|

The stress birefringence of vulcanizates of polyisoprene–polyethylene blends

Abstract: synopsisAs a model for the vulcanizates of block copolymers, mixtures of polyisoprene and polyethylene vulcanized both with a peroxide and with sulfur were investigated by stress birefringence. It was found that the polyethylene dispersion showed a reinforcing effect only in the peroxide vulcanizates. On the other hand, the stress birefringence was decreased with increased polyethylene content except at high polyethylene content.In the latter case, the slope of the line in the birefringence-stress plot was alm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1978
1978
1998
1998

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Improvements in wet skid resistance with SBR/BR tire compounds have also been demonstrated [184]. Nishioka et al [185] have reported that polyethylene acts as a reinforcing agent for IR only when it is chemically linked to the rubber matrix, similar to the hard domains in block copolymers. This is achieved by peroxide vulcanization rather than sulfur.…”
Section: A Physical Mixturesmentioning
confidence: 99%
“…Improvements in wet skid resistance with SBR/BR tire compounds have also been demonstrated [184]. Nishioka et al [185] have reported that polyethylene acts as a reinforcing agent for IR only when it is chemically linked to the rubber matrix, similar to the hard domains in block copolymers. This is achieved by peroxide vulcanization rather than sulfur.…”
Section: A Physical Mixturesmentioning
confidence: 99%